Public Key Infrastructure 5th European PKI Workshop: Theory and Practice, EuroPKI 2008 Trondheim, Norway, June 16-17, 2008, Proceedings - Mjølsnes, Stig F.; Mauw, Sjouke; Katsikas, Sokratis (Security and Cryptology, 2008)
This book constitutes the refereed proceedings of the 5th European Public Key Infrastructure Workshop: Theory and Practice, EuroPKI 2008, held in Trondheim, Norway, in June 2008. The 15 revised full papers presented together with 1 invited paper were carefully reviewed and selected from 37 submissions. Ranging from theoretical and foundational topics to applications and regulatory issues in various contexts, the papers focus on all research and practice aspects of PKI and show ways how to construct effective, practical, secure and low cost means for assuring authenticity and validity of public keys used in large-scale networked services.